ӘДЕБИЙ ШЫҒАРМАЛАРДА КЕЛБЕТЛИКЛЕРДИҢ СТИЛЬЛИК ХЫЗМЕТИ (инглис ҳәм қарақалпақ тили материаллары тийкарында) - Мухаммадияров, А. (ILIM hám JÁMIYET, 2023)
The article deals with the function and role of adjectives in the disclosure of images in English and Karakalpak literary works separately based on the linguocultural aspect.